(untitled) (Journal of Oriental Studies, 2018)
This article is devoted to the study of the influence of educational television and radio programs on the worldview of the Japanese. The purpose of this work is to reveal the features of Japan’s educational television and radio programs that contribute to the personal development of society. The article used the method of content analysis of TV and radio broadcasts and a questionnaire study. Students of bachelor’s and master’s degrees of universities were selected as respondents. Due to close cooperation between KazNU al-Farabi and Japanese universities, the survey was facilitated by teachers and professors from well-known universities in Japan: Waseda University, Tokyo University of Foreign Languages and Tsukuba University. The survey was conducted electronically anonymously, and in the format of an Internet survey. The use of educational television and radio programs in practice, namely in the sphere of studying Japanese language and literature, presumably can increase the level of students’ education, and provide new interactive methods of teaching and learning that will bring the interaction of the media and the educational system to a new level.